Guru Agama Katolik Milenial Di Pusaran Penetrasi Digital Dan Urgensi Pendidikan Kritis - Marianus Mantovanny Tapung (STIPAS St. Sirilus Ruteng, 2019)
Catholic religion teachers have important duties and responsibilities in building the nation’s civilazation. These tasks and responsibilities are becoming increasingly heavy and require information technology that is continously being developed rapidly. To challenge this, Catholic religion teachers need to equip themselves with variety oh knowledge and skills, including digital knowledge and skills also to apply in the world of Catholic religious learning in schools. Catholic learning is more fun, contextual and actual can be harmonized with various digital updates. In addition to making students increasingly understand the material of Catholic religion , but more than that, students are also able to avoid teaching materials with digital development. Catholic teachers can use a variety of digital media to help students live religious life in daily life, and instill these values in the era of digital development.